(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In the present article an analysis of the effects of This on the quality of raw cotton cotton fiber moisture ash. Based on the result of this analysis is the lovely main experiments carried out by researchers, and recommendations are given for the use of technological processes and steam’ve moistening of cotton and fiber.